Health Citizenship and Healthcare Access in Indonesia, 1945-2020 - Arief Priyo Nugroho; Sri Handayani; Diyan Ermawan Effendi (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Health citizenship is understood over how the government provides access to healthcare. This paper aims to describe the development of health citizenship from the post-colonial until the democratization era in Indonesia by analyzing health accessibility. The social-history approach was applied to analyze contemporary study in Indonesian healthcare access from 1945 to 2020. This article analyses the dynamic over political regime changes context and its approach to deal with health accessibility based on acceptability, availability, and affordability issues. This study found that each political regime provides a different social-political context in prioritizing and administrating the accessibility of healthcare. Besides each regime appears issues of accessibility, all of which provoke inequity in healthcare. This paper argues that health citizenship development in Indonesia shows the underlying cause of inequity. Consequently, the minimal presence of public participation raises inequity. Inequity leads to healthcare access that provides pointless improvement. Narratives in health citizenship fulfillment call for public participation space in administering access to healthcare.